Beteendebudget och hägnutnyttjande hos jaguarer (Panthera onca) på Parken Zoo i Sverige - Johansson, Evelina (2016)
The staff at Parken Zoo in Sweden have noticed that their jaguars are performing stereotypic behaviour. This behaviour has been seen performed mostly by the male but it can be performed by the females too. The staff have seen tendencies that the zoo’s Asian lions may have an effect on the male jaguar’s pacing behaviour. Captive carnivores are said to be the group of animals that are more prone to perform this kind of behaviour, where pacing is the most common stereotype in this animal group. There are lots of theories why stereotypes occur in captive carnivores and the most common one is that the behaviour develops from the absence of being able to perform their natural feeding behaviour. Studies have shown that visitor intensity and visitor density have a significant effect on jaguars’ pacing. Three jaguars where observed in this study, one male and two females. The animals were observed for 10 days, where their behaviour and enclosure use were registered. To see if the lions affected the jaguars, the two first observations each day were performed before and after the lions were let out into their outdoor enclosure. Every second day the lions were let out and the rest of the days they were already outside when the jaguars were let out to their outdoor enclosure. During the observations it became obvious that the male jaguar often vocalized while performing pacing by the fence closest to the lions. This could be explained by the hypothesis that the male jaguar’s pacing has developed from a territorial behaviour, like he feels the need to defend his territory from the lions. Pacing was also performed by one of the females in relation to two school-classes of young and noisy children. An explanation to this could be that she was trying to get away from an aversive stimuli, since she performed pacing along the fence farthest away from the children. The results points towards that the lions increased the frequency of pacing in the male jaguar, but there was too little data to draw any definite conclusion. The behaviour observations showed that lying down was the most common behaviors performed by the females. Lying down and walking were the most common behaviour by the male. Pacing was the third most common behavior performed by the male. The results of observations devoted to enclosure use showed that the jaguars used their enclosure well but a few places are favoured by the different individuals.